Antimicrobial Peptide Structures: From Model Membranes to Live Cells. Issue 2 (30th November 2017) - Sani, Marc‐Antoine; Separovic, Frances
Abstract: The rise in antibiotic resistance has led to a renewed interest in antimicrobial peptides (AMPs) that target membranes. The mode of action of AMPs involves the disruption of the lipid bilayer and leads to growth inhibition and death of the bacteria. However, details at the molecular level of how these peptides kill bacteria and the reasons for the observed differences in selectivity remain unclear. Structural information is crucial for defining the molecular mechanism by which these peptides recognize, self‐assemble and interact with a particular lipid membrane. Solid‐state NMR is a non‐invasive technique that allows the study of the structural details of lipid–peptide and peptide–peptide interactions. Following on from studies of antibiotic and lytic peptides, gramicidin A and melittin, respectively, we investigated maculatin 1.1, an AMP from the skin of Australian tree frogs that acts against Gram‐positive bacteria. By using perdeuterated phospholipids and specifically labelled peptides, 2 H, 31 P and { 31 P} 15 N REDOR solid‐state NMR experiments have been used to localize, maculatin 1.1 in neutral and anionic model membranes. However, the structure, location and activity depend on the composition of the model membrane and current advances in solid‐state NMR spectroscopy now allow structure determination of AMPs in live bacteria. Abstract : Investigating peptides : Developments in biological solid‐state NMR have led to structure determination of membrane‐active peptides in cell membranes.